Hidden deficiency under bright skies: Vitamin D prevalence and genetic associations in African Type 2 diabetes: A systematic review and meta-analysis - Eyob Girma Abera; Samuel Alemu Himbaro; Surafel Worku Megersa; Tesfaye Adugna Leta; Ermias Habte Gebremichael (PLoS ONE, 2026)
Background Type 2 diabetes mellitus (T2DM) has become a significant health challenge in Africa, with rapidly increasing prevalence. Despite abundant sunlight, vitamin D deficiency (VDD) is prevalent and may influence glucose metabolism and insulin resistance. Genetic factors, including vitamin D receptor (VDR) polymorphisms, may modify these effects. This systematic review and meta-analysis aimed to estimate the prevalence of VDD and evaluate the association of VDR gene variants with T2DM among African populations. Methods We systematically searched PubMed, Cochrane Library, ScienceDirect, Embase, Web of Science, and Google Scholar for observational studies published up to June 11, 2025, reporting VDD prevalence and VDR genetic associations in African individuals with T2DM. Data extraction and quality assessment followed Joanna Briggs Institute (JBI) and PRISMA 2020 guidelines. Pooled prevalence, mean difference and odds ratios (ORs) were calculated using random-effects meta-analysis. Heterogeneity, publication bias, sensitivity analyses, and meta-regression were performed. All statistical analyses were conducted using R version 4.3.1 (2023-06-16 ucrt). Results Twenty-two eligible studies encompassing 3,447 participants from 11 African countries were included. The pooled prevalence of VDD among individuals with T2DM was 51% (95% CI: 36–65%), with substantial heterogeneity (I 2 = 95.7%). Subgroup analyses showed highest prevalence in East Africa (56%). Vitamin D-deficient individuals had significantly higher HbA1c compared to sufficient individuals (mean difference = 0.89%; 95% CI: 0.06–1.72 p = 0.044; I 2 = 0%, p = 0.49). The pooled analysis of VDR FokI polymorphisms did not demonstrate a significant association with T2DM risk (OR = 1.51; 95% CI: 0.23–9.73). No evidence of publication bias was detected. Conclusion Vitamin D deficiency is highly prevalent in African populations with T2DM and is associated with poorer glycemic control. Current evidence is insufficient to conclude on VDR FokI polymorphisms and T2DM risk. These findings underscore the need for interventional trials to determine whether improving vitamin D status enhances glycemic outcomes; routine screening or supplementation recommendations remain premature. Registration number CRD420251134616.